Analysis of the Current Situation and Problems of Technical Personnel in Material Production Enterprises - Sun, Huayun (Journal of Theory and Practice of Management Science, 2024)
With the rapid development of high- temperature industry, our country has become the largest country in the world in the production, consumption and export of refractory products. However, the technical quality of front-line employees in refractory enterprises is generally low. Especially with the continuous upgrading of refractory production equipment, process and quality control, the problem of lack of technical and skilled personnel is becoming more and more serious. From the perspective of human resources, and in-depth investigation on the development of refractory industry and its personnel status, the current situation and problems of refractory enterprise technical personnel are analyzed. It is found that leading large enterprises are still in short supply of high-tech application-oriented technical personnel and operational personnel even though the structure of senior technical personnel is relatively reasonable, and small and medium-sized Enterprises gradually enter into a vicious circle of low wages, low technology, low labor productivity because they only focus on production, not research. In addition, vocational students working in different refractory enterprises often face a dilemma, some feeling lack of relatively complete theoretical knowledge, some wanting to improve the ability to operate and deal with faults.